Сучасні науково-методичні проблеми математики у вищій школі - Національний університет харчових технологій (My University, 2022)
Видання містить матеріали Всеукраїнськьої науково-методичної конференції «Сучасні науково-методичні проблеми математики у вищій школі». На конференції розглянуті сучасні математичні методи в інженерних задачах та методичні проблеми викладання математичних дисциплін у вищій школі. У матеріалах висвітлено шляхи і методи інтенсифікації навчального процесу й вплив новітніх наукових розробок на формування майбутніх фахівців. The publication contains materials of the All-Ukrainian scientific-methodical conference "Modern scientific-methodical problems of mathematics in higher school". The conference discusses modern mathematical methods in engineering problems and methodological problems of teaching mathematical disciplines in higher education. The materials highlight the ways and methods of intensifying the educational process and the impact of the latest scientific developments on the formation of future professionals.
Keywords: математичні методи; математична освіта; інженерні задачі; нелінійні рівняння; mathematical methods; mathematical education; engineering problems; nonlinear equations